The Efficaccy of Roundtable Technique on EFL Students' Writing Skills: An Experience Learned from a Remote Area: Roundtable and wrtiting skills - Jusmin HJ Wahid; Iwan Irawan; Shuai Ma; Moh Julfandi Koroy (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Writing is a skill to express ideas and thoughts to make a message explicit. To arrange an idea in written text the students’ need soft skill in completing a text; grammar, punctuation, and vocabulary are the most important aspect in the writing skill that should be mastered by the students organizing the ideas. To attain the students' comprehend and overcome the obstacles in the writing skill, the researchers implementing a roundtable technique in the teaching process.The research aims to investigate the efficacy of the roundtable technique on EFL students' writing skills. Then, the researchers implement quasi-experimental design, Totally 46 students in each class. In addition, the researchers implement writing test as research instrument. The finding showed that the Roundtable technique is an effective way to improve students' writing skills and can stimulate students' attention to the writing skills. In addition, students found their identity and were more confident in elaborating the good ideas. The two classes proved that the significance of the experimental class is higher than the control and the significant score is 0.0. This means that the roundtable technique is an effective way to implement in the classroom. It can encourage students to more focus on the issue and update the new information to improve their writing skills. Moreover, it is an enjoyable technique to implement in the classroom to create a good atmosphere and can improve students' attention in the writing process. Roundtable As a recommended solution to the English teachers and lecturers in prioritize to students writing skills. These is design to specifically improve students' grammar, punctuation, and vocabulary mastery in writing skills.